Considering Space : A Critical Concept for the Social Sciences. - Bartmanski, Dominik; Füller, Henning; Hoerning, Johanna; Weidenhaus, Gunter (Milton : Taylor & Francis Group, 2023)
Showing how society can and should be perceived as spatial, this book demonstrates what has changed in the perception of space within the social sciences and how useful - indeed indispensable - concepts of space and spatial concepts remain today.
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Table of Contents -- List of Illustrations -- List of Contributors -- 1 Introduction: An Invitation to Spatial Theorizing -- Part I: Considering Space in Social Theory -- 2 Understanding Social Change: Refiguration -- 3 Space in the Theory of Reflexive Modernization: The Location of Subjects from a Cosmopolitan Perspective -- 4 Wittgenstein's House: From Philosophy to Architecture to Philosophy -- 5 Mapping Assemblages: Analytical Benefits of Thinking with Space -- 6 The Invention of the Global: Constitutions of Space in Theories of Globalization -- Part II: Considering Space in Global Epistemologies -- 7 Dividing the 'World': Spatial Binaries in Global Perspective -- 8 European Elsewheres: Global Sociologies of Space and Europe -- 9 The Refiguration of the Social and the Re-Configuration of the Communal -- 10 Caste, Class and Space: Inequalities in India -- Part III: Considering Space in Meaning Making -- 11 A Dangerous Liaison? Space and the Field of Cultural Production -- 12 Object Affordances, Space, and Meaning: The Case of Real Estate Staging -- 13 Like a Child in a Supermarket: Locational Meanings and Locational Socialisation Revisited -- 14 Placing Performance into a Distressed Space: The Case of San Berillo -- 15 Epilogue -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books